ENGLISH CORPORA RESEARCH: THE MEANING OF CREATIVE AND WRITING CONTEXTS IN IWEB APLICATION - Perdana Prasetya, Eska (ENGLISH JOURNAL, 2021)
Corpus linguistics learns about language with the help of modern computer technology in language data collection. language corpora are one of the important aspects related to langaunge corpora is a matter of copyright, especially if the findings from the corpus will be disseminated through handouts or published in any form.The research explored the field of computational linguistics to find the meaning of Creative Writing Context in online learning during pandemic. Corpus-based research is also considered as a broad approach to qualitative research or as a method for gathering qualitative data. more than 1 million sentences that connect creative words with writing. Broadly speaking, if we are looking for creative words, it will be related to writing.